De-industrialisation in the world's factory: a microscopic analysis of the restructuring of Wuhan Iron and Steel Company (WISCO), Wuhan, China. Issue 1 (1st January 2022) - Miao, Julie Tian; Phelps, Nicholas; Li, Zhigang; Lin, Sainan
Abstract : Analysis of deindustrialisation remains dominated by studies of the OECD countries. The process has only recently been studied in newly industrialised countries and regions yet in a geographically constrained manner, dominated by macro-level, sectorial-based analytical frameworks. China so far has not featured highly in this emerging literature as its deindustrialisation is a more recent phenomenon overshadowed by ongoing industrialisation. This article contributes to an understanding of deindustrialisation in a microscopic empirical analysis of a China case. The microscopic approach is particularly relevant in China where state-owned, self-contained enterprises, or ' danweis ', used to shape the industrial and social lives of urban Chinese, but it is also relevant to understanding processes of deindustrialisation elsewhere where these involve iconic, single industry or company communities. Adopting a case-study ethnographic approach, this study examines the transformation experienced by the iconic Wuhan Iron and Steel Company (WISCO) in Wuhan, Central China, and reveals variations in the pace of change in industrialisation and the 'half-life' of deindustrialisation as it is moderated by the institutionalisation and social life of danweis in China.